Advances in Cartography and GIScience. Volume 2 Selection from ICC 2011, Paris - Ruas, Anne (Publications of the International Cartographic Association (ICA), 2011)
This book is comprised of a  selection of the best papers presented during the 25th International Cartography Conference which was held in Paris between 3rd and 8th July 2011. The scope of the conference covers all fields of relevant GIS and Mapping research subjects, such as geovisualization, semiotics, SDI, standards, data quality, data integration, generalization, use and user issues, spatio-temporal modelling and analysis, open source technologies and web services, digital representation of historical maps, history of GIS and cartography as well as cartography for school children and education.